Analysis of ice shelf flexure and its InSAR representation in the grounding zone of the southern McMurdo Ice Shelf - W. Rack; M. A. King; O. J. Marsh; C. T. Wild; D. Floricioiu (The Cryosphere, 2017)
We examine tidal flexure in the grounding zone of the McMurdo Ice Shelf, Antarctica, using a combination of TerraSAR-X repeat-pass radar interferometry, a precise digital elevation model, and GPS ground validation data. Satellite and field data were acquired in tandem between October and December 2014. Our GPS data show a horizontal modulation of up to 60 % of the vertical displacement amplitude at tidal periods within a few kilometres of the grounding line. We ascribe the observed oscillatory horizontal motion to varying bending stresses and account for it using a simple elastic beam model. The horizontal surface strain is removed from nine differential interferograms to obtain precise bending curves. They reveal a fixed (as opposed to tidally migrating) grounding-line position and eliminate the possibility of significant upstream bending at this location. The consequence of apparent vertical motion due to uncorrected horizontal strain in interferometric data is a systematic mislocation of the interferometric grounding line by up to the order of one ice thickness, or several hundred metres. While our field site was selected due to its simple boundary conditions and low background velocity, our findings are relevant to other grounding zones studied by satellite interferometry, particularly studies looking at tidally induced velocity changes or interpreting satellite-based flexure profiles.